Serotype conversion gene rfbT is directly regulated by histone-like nucleoid structuring protein (H-NS) in V. cholerae O1 - Han, Yu; Li, Jing; Gao, He; Li, Xiaorui; Duan, Ran; Cheng, Qian; Kan, Biao; Liang, Weili (Frontiers in Microbiology, 2023)
Vibrio cholerae serogroup O1 (V. cholerae O1) is closely associated with cholera epidemics and has two main immunologically distinguishable serotypes, Ogawa and Inaba. Isolates serotype as Ogawa if the O-antigen polysaccharide (O-PS) is methylated or as Inaba if the O-PS is not methylated. This methylation is mediated by a methyltransferase encoded by the rfbT gene, and the mutation and low expression of rfbT results in serotype switch from Ogawa to Inaba. Previously, we have showed that cAMP receptor protein (CRP) transactivates rfbT. In this study, we demonstrated that histone-like nucleoid structuring protein (H-NS) is directly involved in the transcriptional repression of rfbT. This finding is supported by the analyses of rfbT mRNA level, rfbT-lux reporter fusions, electrophoretic mobility shift assay (EMSA) and DNase I footprinting assay. The rfbT mRNA abundances were significantly increased by deleting hns rather than fis which also preferentially associates with AT-rich sequences. A single-copy chromosomal complement of hns partly restored the down-regulation of rfbT. Analysis of rfbT-lux reporter fusions validated the transcriptional repression of hns. Subsequent EMSA and DNase I footprinting assay confirmed the direct binding of H-NS to rfbT promoter and mapped the exact binding site. Furthermore, we found that in hns deletion mutant, CRP is no longer required for transactivating rfbT, suggesting that the primary role of CRP is probably to displace H-NS to derepress rfbT expression. Together, this study expanded our understanding of the genetic regulatory mechanism of serotype conversion by global regulators in V. cholerae O1.